Implementasi Program Tahfidz Al-Qur’an di SMA Muhammadiyah Pacitan - Isnawati, Nani; Hudha, Mokhamad Choirul (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2024)
The methods used to memorize the Al-Qur'an include: Talqin method, tasmi', muroja'ah, tafsir and tadjwid. This article discusses the implementation of the Al-Qur'an memorization program at SMA Muhammadiyah Pacitan. The aim is to describe the planning, implementation and evaluation of Al-Qur'an memorization learning at SMA Muhammadiyah Pacitan. This type of research is qualitative descriptive with a field research research method. Research subjects were determined using purposive sampling techniques. The data collection techniques are observation, interviews and documentation. The results of the study show that the implementation of the Al-Qur'an memorization program at SMA Muhammadiyah Pacitan is carried out in groups based on the level of ability to read the Al-Qur'an in each class, with one accompanying teacher. The learning method uses the Talqin, Tahsin methods, while the evaluation method is muroja'ah and tasmi'. The program is held every day at school hours starting 1 hour before KBM (teaching and learning activities), with a 1-year program memorizing 1 Juz starting from juz 30, 28, and 29. To support this program, the Educational Institution collaborates with the El-Yamin Al-Qur'an Friendship Foundation. Tasmi' is held once per juz both online and offline. At the end of the semester, a tahfidz report is submitted to parents as a form of accountability.